Children and childhoods in L.M. Montgomery continuing conversations - Bode, Rita 1950-; Clement, Lesley D. 1951-; Pike, Elizabeth Holly 1958-; Steffler, Margaret 1953- (McGill-Queen's University Press, 2022)
"From Jane Austen to contemporary fanfiction and adaptations, literary portrayals of the child and imaginings of childhood are particularly telling indicators of cultural values and when they shift. Inspired by the responsive reading practices of L.M. Montgomery herself, those demonstrated by her characters and her diverse readership, Children and Childhoods in L.M. Montgomery works with concepts of confluence, based on organic, non-linear readings of texts across time and space. Such readings reconsider views of childhood and children by challenging power hierarchies and inequities found in approaches that privilege more linear readings of literary influence. While acknowledging differences between childhood and adulthood, contributors emphasize kinship between child and adult as well as between past and present selves and use both scholarly approaches and creative reimagining to explore how the boundaries between different stages of life are blurred in Montgomery's writing. Children and Childhoods in L.M. Montgomery addresses Montgomery's challenges to prescribed assumptions about childhood, while positioning her novels as essential texts in twenty-first century literary, childhood, and youth studies."--
Keywords: Montgomery, L. M. -- 1874-1942; Kind -- Motiv; Montgomery, L. M. / (Lucy Maud) / 1874-1942 / Criticism and interpretation; Children in literature; Canadian literature / 20th century / History and criticism; Canadian literature (English) / 20th century / History and criticism; Montgomery, L. M. / (Lucy Maud) / 1874-1942; Criticism, interpretation, etc; Literary criticism; Aufsatzsammlung